2017
DOI: 10.1177/1010428317695925
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of bach1 gene by small interfering RNA–mediation regulates invasive and expression level of miR-203, miR-145, matrix metalloproteinase-9, and CXCR4 receptor in MDA-MB-468 breast cancer cells

Abstract: Background: Recently experimental validation of the networks revealed bach1, a basic leucine zipper transcription factor, as the common regulator of several functional invasive genes. The expression of bach1 and its target genes was linked to the higher risk of breast cancer recurrence in patients. The aim of this study was to investigate the effect of specific bach1 small interfering RNAs, on the invasive and expression level of miR-203, miR-145, matrix metalloproteinase-9, and CXCR4 receptor which play a rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…An increasing number of studies have reported that miR‐203 is frequently downregulated in numerous types of cancer cells, such as osteosarcoma, colorectal cancer, hepatocellular carcinoma, breast cancer, and NSCLC cells. Changes in the expression of miR‐203 results in antitumor effects, suggesting that miR‐203 plays an important role in regulating tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have reported that miR‐203 is frequently downregulated in numerous types of cancer cells, such as osteosarcoma, colorectal cancer, hepatocellular carcinoma, breast cancer, and NSCLC cells. Changes in the expression of miR‐203 results in antitumor effects, suggesting that miR‐203 plays an important role in regulating tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…CXCR4 is known to increase cell migration ability and promote cancer metastasis ( 102 , 103 ). BACH1 has been reported to promote the expression of CXCR4 in colorectal ( 81 ) and breast cancers ( 75 , 99 , 104 ). However, no published study has examined whether or not BACH1 directly regulates CXCR4 .…”
Section: Functions Of Bach1 In Cancer Metastasismentioning
confidence: 99%
“…Other studies have demonstrated that common MMP-7 genetic polymorphisms are significant determinants of survival in Chinese patients with breast cancer (33). Overexpression of MMP-9 induced by the inflammatory cytokine interleukin-1β can promote MCF-7 cell metastasis, and the inhibition of MMP-9 can inhibit breast cancer cell metastasis (34)(35)(36)(37). Further studies indicated that MMP-9 is regulated by the NF-κB pathway, and that inhibition of MMP-9 via the NF-κB signaling pathway can suppress the MCF-7 cell invasion ability (38)(39)(40)(41).…”
Section: Bcsc-1 Immunostaining [N (%)] ------------------------------mentioning
confidence: 99%